Talus Fracture – a Pathomechanical Study Using Finite Element Analysis - Mongkol Kaewbumrung; Chayanin Angthong; Prasit Rajbhandari; Naruebade Rungrattanawilai (Ortopedia Traumatologia Rehabilitacja, 2025)
BACKGROUND: The talus is a peculiar bone in the human body that plays a key role in load transfer due to its unique shape and characteristics. Fractures involve challenging treatment and potential complications. We aimed to simulate the talus using real-world data and analyze its biomechanical responses to potential forces that might cause its fracture. MATERIAL AND METHODS: We retrieved a three-dimensional (3D) file of the intact talus, submitted it to a 3D finite element analysis (FEA) using software (ANSYS Mechanical V2023R2), and then set the elastic modulus or Young's modulus values of the talus based on a previous study. To analyze talar fractures, we employed both positive and negative force directions to examine fracture behavior. The talar configurations were 0 , 15, 30, and 45 cases. Force applied in the y-direction compressed the top of the talus. The bottom surface of the talus, subjected to compression, supports the boundary conditions that mimic realistic talus motion mechanics. RESULTS: FEA demonstrated that the neck of the talus exhibited the highest magnitude of total deformation, suggesting susceptibility to crack initiation. A sudden increase in force in the positive direction increased the likelihood of a talar fracture. Stress analysis depicted the maximum equivalent (von Mises) stress on the talus, indicating that the highest stress occurred when the force was applied in the positive direction, particularly at 15 (posterosuperior to the anteroinferior direction). Our analysis underscores that the angle of force is the primary contributor to talar fractures. CONCLUSION: Our 3D FEA study concluded that the talar neck area was the most vulnerable to fracture in the axial force simulation, especially in the 15 force direction. Safety measures should be implemented for people performing risky activities related to axial force injuries.
Keywords: Foot and Ankle Surgery; Lower Extremity Biomechanics and Pathologies; Diabetic Foot Ulcer Assessment and Management